Diversifikasi Produk Olahan Ikan Wader dan Manajemen Usaha Berbasis Marketing Online di BUMDes Margosari, Kulon Progo - Agus Setiyoko; Rosalia Prismarini Nurdiarti; M Nastain (Institut Pertanian Bogor, 2022)
Margosari village has the Serang River which is a source of income for the community. The catched fish is sold in the form of fresh wader fish at a price of Rp. 7,000.00 to Rp. 9,000.00 / Kg. Selling price and storage capacity of wader fish are very low, so it needs to be increased by diversifying the process into krispi wader as one of the business opportunities. The problems faced by partners are: 1) Limited knowledge and skills regarding the diversification process of wader fish; 2) Packaging method is still simple and does not meet standards; and 3) Marketing process is still carried out by direct selling and has not used online marketing method. This community service program aims to increase knowledge and skills regarding the diversification process of wader fish into krispi wader, packaging technology and online marketing. The methods used in conducting this program were in the form of counseling and training as well as assistance to 20 BUMDes members. Counseling and training activities include: 1) Counseling and training on the diversification of processed wader fish into krispi wader fish; 2) Counseling and packaging training was held to know how to pack and making packaging labels; 3) Marketing training based on online marketing. The benchmarks for the success of this service activity can be seen from the increasing of knowledge and skills regarding the diversification of wader krispi process, knowledge of labels and packaging as well as knowledge of online marketing for members of the Margosari BUMDes group based on pretest and posttest analysis of service activities. The conclusion of this service activity is that the counseling method followed by training methods are effective for members of the Margosari BUMDes group in diversifying their wader fish, labeling and packaging as well as online marketing.